Flies Density Level in the Nutrition Installation of M. Th Djaman Sanggau Regional General Hospital - Khansa Atallah Puruhita; Hajimi; Jaleha (POLTEKKES KEMENKES PONTIANAK, 2021)
Nutrition installation at M. Th. Djaman Sanggau hospital was in charge of providing the food service needs of the patients. Nutritional installations as a place for storing, processing, serving, and distributing food, could attractted the presence of flies and pose a risk of contamination. Its location was close to the incinerator, morgue, and garbage dump. This study aimed to describe the flies density level in the Nutrition Installation of M. Th. Djaman Sanggau hospital. This research type was an observational study with a descriptive approach, which described the flies density level in the Nutrition Installation of M. Th. Djaman Sanggau hospital. Data collection was done by interview and observation. The data obtained were presented in tabular form, described, and explained in narrative form. From the study results, it was found that the flies density level in the Nutrition Installation of M. Th. Djaman Sanggau hospital was 1.13 tails per block grill with the results had met the requirements. The average measurement results for temperature figures were 28°C, humidity 75.8%, and lighting intensity 223.7 LuxIt was necessary to control the flies density level in the garbage dump container at M. Th. Djaman Sanggau hospital, by improving the sanitation and hygiene of those, spraying insecticides, and improving waste management. In addition, to reduce the density of flies in the nutrition installation of M. Th. Djaman Sanggau hospital, it was necessary to prevent access to flies by closing doors and windows, using fly barrier curtains, closing waste water disposal, and to improve sanitation hygiene